A Variant in the IRF6 Promoter Associated with the Risk for Orofacial Clefting. (July 2023) - Li, M.-J.; Kumari, P.; Lin, Y.-S.; Yao, M.-L.; Zhang, B.-H.; Yin, B.; Duan, S.-J.; Cornell, R.A.; Marazita, M.L.; Shi, B.; Jia, Z.-l.
The single-nucleotide polymorphism (SNP) rs2235371 ( IRF6 V274I) is associated with nonsyndromic cleft lip with or without cleft palate (NSCL/P) in Han Chinese and other populations but appears to be without a functional effect. To find the common etiologic variant or variants within the haplotype tagged by rs2235371, we carried out targeted sequencing of an interval containing IRF6 in 159 Han Chinese with NSCL/P. This study revealed that the SNP rs12403599, within the IRF6 promoter, is associated with all phenotypes of NSCL/P, especially nonsyndromic cleft lip (NSCLO) and a subphenotype of it, microform cleft lip (MCL). This association was replicated in 2 additional much larger cohorts of cases and controls from the Han Chinese. Conditional logistic analysis indicated that association of rs2235371 with NSCL/P was lost if rs12403599 was excluded. rs12403599 contributes the most risk to MCL: its G allele is responsible for 38.47% of the genetic contribution to MCL, and the odds ratios of G/C and G/G genotypes were 2.91 and 6.58, respectively, for MCL. To test if rs12403599 is functional, we carried out reporter assays in a fetal oral epithelium cells (GMSM-K). Unexpectedly, the risk allele G yielded higher promoter activity in GMSM-K. Consistent with the reporter studies, expression of IRF6 in lip tissues from NSCLO and MCL patients with the G/G phenotype was higher than in those from patients with the C/C phenotype. These results indicate that rs12403599 is tagging the risk haplotype for NSCL/P better than rs2235371 in Han Chinese and supports investigation of the mechanisms by which the allele of rs12403599 affects IRF6 expression and tests of this association in different populations.